Processing Collective Wounds, Weaving Networks among Generations: An Art Therapy Experience in Chile - Pamela Reyes; Selma Ciornai (Arteterapia)
The text deals with the process of development and application experience of art-therapy areas in social and community, working with the recent history of Chile. It contributes from art therapy to encounter and the development of the diversity of experiences in this country and plant the collective memory as the construction of a common memory built from the possibility of sharing, unite and express the diversity of personal experiences.